Monthly Trends in the Life Events Reported in the Prior Year and First Year of the COVID-19 Pandemic in New Zealand - Howard, Chloe; Overall, Nickola C.; Sibley, Chris G. (Frontiers in Psychology, 2022)
The current study examines changes in the economic, social, and well-being life events that women and men reported during the first seven months of the COVID-19 pandemic. Analyses compared monthly averages in cross-sectional national probability data from two annual waves of the New Zealand Attitudes and Values Study collected between October 2018–September 2019 (N = 17,924), and October 2019–September 2020 (N = 41,653), which included the first seven months of the pandemic (Mar–Sep 2020). Results indicated that people (particularly women) reported increased job loss in the months following an initial COVID-19 lockdown relative to the same months the year earlier. Women also experienced an increase in family troubles when restrictions eased and reported increased negative lifestyle changes that persisted throughout the first seven months of the pandemic. The proportion of people experiencing many other life events (e.g., mental health, financial concerns) in New Zealand did not differ reliably from the pre-pandemic monthly baseline. These results highlight resilience to many potential negative life events within the first seven months of the COVID-19 pandemic. However, the pandemic did not affect everyone equally, and the burden of increased negative events appears more heavily borne by women. As the pandemic continues more than 18 months from initial community transmission of COVID-19, our findings provide important insight into the impact of the pandemic on potential negative life events, especially among women, that may have critical consequences for mental health, gender equality, and social well-being over time.